Success and Failure of Revolutions in Lebanon - Nader, Sarah (2022)
On October 17, 2019 thousands of people took to the streets all over Lebanon to protest against the economic situation and the corrupt practices of the Lebanese government and Lebanon’s ruling elite. The protestors called for the resignation of the Lebanese parliament, the cabinet and the president of the republic whom they accused of bearing responsibility for the economic crisis gripping the country. The protesters further demanded the introduction of major political and socioeconomic reforms. Only a few of the objectives of the protestors were met. A few months after its onset, the “October 17th Revolution” lost its momentum and the economic crisis in Lebanon intensified. This thesis aims to understand why Lebanon’s “October 17th Revolution” failed to achieve most of its objectives although, at the outset, several political observers expected it to succeed. This thesis further investigates two prior revolutions that can be considered successful ones: the 1952 revolution (that ousted then President Bishara El-Khoury) and the 2005 Cedar Revolution that led to the withdrawal of the Syrian army from Lebanon. The thesis contends that by comparing these two past revolutions with the “October 17 Revolution”, one can identify the factors that were responsible for the failure of the “October 17 Revolution”. These factors can be traced to: 1) the entrenched power of the ruling sectarian elite, 2) the nature of the demands and the strategies of the protestors, 3) the role played by the army and the security forces, and 4) the role of external players.